Forensic profiling of proprietary pseudoephedrine precursors and oxidative products in tandem with chemometric analysis - Nadzri, Ainol Hayah Ahmad (2023)
Pseudoephedrine (PSE) precursors are rampantly abused for the illicit production of synthetic drugs. Clandestine chemists can access this substance either from illegal sources or clandestinely extracted from proprietary formulations despite efforts from manufacturers to limit the PSE’s re-extraction. While the reduction reaction of PSE will produce methamphetamine (MA), the oxidation reaction will afford methcathinone (MET), a new psychoactive stimulant (NPS). MET is currently gaining attention as a possible replacement for MA drugs; however, there is a minimal report in the scientific literature regarding the analysis of this substance, particularly regarding its organic and isotopic profiles, which may limit the forensic community's ability to detect and regulate this substance. Initial studies involved optimisation of PSE extraction from various proprietary sources, followed by characterisation and forensic profiling of the extracted PSE products. Acid-base extraction proved to be the most viable method to obtain considerably pure PSE. Subsequently, five different sources of simulated PSE precursors were oxidised following two clandestine synthetic routes, namely chromate and manganate routes. The synthesised oxidative products were then forensically characterised, followed by an examination of their organic and isotopic profiles. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy and gas chromatography-mass spectrometry (GC-MS) were used for organic impurity profiling, while isotope ratio mass spectrometry (IRMS) profiles 13C:12C and 15N:14N stable isotopes. The chromate and manganate routes produce compounds specific to U1 (RT 5.701, m / z 51, 77, 105, 91, and 207) and U3 (RT 9.013, m/z 70, 85, 117). Additionally, unreacted PSE was found in all the samples from the manganate route. Isotope analysis of 13C:12C and 15N:14N ratios differentiated the samples by the synthetic route and precursor sources with a nitrogen isotope, providing the best results. Data from ATR-FTIR spectra and GC-MS chromatograms were used in conjunction with chemometric analysis, namely hierarchical cluster analysis (HCA), principal component analysis (PCA), and linear discriminant analysis (LDA), to investigate the sources of precursors and the synthetic routes used. The best grouping results are obtained from LDA, where all PSE samples extracted from different sources are traced back to the source, and MET are successfully differentiated based on their synthetic routes and sources of PSE precursor used. Based on the FTIR data set, LDA recorded the correct classification rate for PSE and MET samples of 90.0% and 78.6%, respectively, while for GC-MS datasets, LDA recorded a correct classification rate of 100% for PSE and 95.2% for the MET samples. Forensic chemical profiling in tandem with chemometric analysis is beneficial in advocating the type of precursor and synthetic route used for drug manufacturing in illicit laboratories.